[RETRACTED] Negative pressure wound therapy versus conventional dressing for open fractures in lower extremity trauma: a multicentre randomized controlled trial. (July 2020) - Tahir, Muhammad; Chaudhry, Ejaz A.; Zimri, Faridullah K.; Ahmed, Nadeem; Shaikh, Saeed A.; Khan, Shoaib; Choudry, Usama K.; Aziz, Amer; Jamali, Allah R.
Abstract : Aims: It has been generally accepted that open fractures require early skeletal stabilization and soft-tissue reconstruction. Traditionally, a standard gauze dressing was applied to open wounds. There has been a recent shift in this paradigm towards negative pressure wound therapy (NPWT). The aim of this study was to compare the clinical outcomes in patients with open tibial fractures receiving standard dressing versus NPWT. Methods: This multicentre randomized controlled trial was approved by the ethical review board of a public sector tertiary care institute. Wounds were graded using Gustilo-Anderson (GA) classification, and patients with GA-II to III-C were included in the study. To be eligible, the patient had to present within 72 hours of the injury. The primary outcome of the study was patient-reported Disability Rating Index (DRI) at 12 months. Secondary outcomes included quality of life assessment using 12-Item Short-Form Health Survey questionnaire (SF-12), wound infection rates at six weeks and nonunion rates at 12 months. Logistic regression analysis and independent-samples t- test were applied for secondary outcomes. Analyses of primary and secondary outcomes were performed using SPSS v. 22.0.1 and p-values of < 0.05 were considered significant. Results: A total of 486 patients were randomized between January 2016 and December 2018. Overall 206 (49.04%) patients underwent NPWT, while 214 (50.95%) patients were allocated to the standard dressing group. There was no statistically significant difference in DRI at 12 months between NPWT and standard dressing groups (mean difference 0.5; 95% confidence interval (CI) -0.08 to 1.1; p = 0.581). Regarding SF-12 scores at 12 months follow-up, there was no significant difference at any point from injury until 12 months (mean difference 1.4; 95% CI 0.7 to 1.9; p = 0.781). The 30-day deep infection rate was slightly higher in the standard gauze dressing group. The non-union odds were also comparable (odds ratio (OR) 0.90, 95% CI 0.56 to 1.45; p = 0.685). Conclusion: Our study concludes that NPWT therapy does not confer benefit over standard dressing technique for open fractures. The DRI, SF-12 scores, wound infection, and nonunion rates were analogous in both study groups. We suggest surgeons continue to use cheaper and more readily available standard dressings. Cite this article: Bone Joint J 2020;102-B(7):912–917.